Music in Late Medieval Bruges - Strohm, Reinhard (Oxford Clarendon Press, 1985)
The musical achievements of the so-called Franco-Flemish School' have attracted many writers, yet Bruges itself has still to be put back on the map of European music history. This book describes how the people of Bruges shaped their acoustic environment and gave musical expression to their spiritual needs. It is based on a scrutiny of musical sources, stylistic trends in music, composers' achievements, and the function of musical genres; all these are seen against a reconstruction, from archival sources, of the socio-economic context of the art of music - an art which, in all its various manifestations, high' and low', sacred and secular, courtly and civic, polyphonic and monophonic, mirrors later medieval urban culture as a whole.
Keywords: Middle Ages (500-1400); Music history; Bruges (Belgium)